Research features of low-fat ice cream mixtures structuring with β-glucan and pectin-containing vegetable raw materials - Mykhalevych, Artur; Sapiga, Victoria; Polishchuk, Galyna (My University, 2022)
A study of the viscosity-speed characteristics of ice cream mixes was conducted using a rotary viscometer with a "cylinder-cylinder" measuring system. Shear stress τ (Pa) was measured at a temperature of 20°C for twelve values of the shear rate gradient in the range from 3 to 1312 s-1 in forward and reverse motion.
Keywords: ice cream; hydrocolloids; vegetable puree; морозиво; гідроколоїди; овочеве пюре; кафедра технології молока і молочних продуктів